Spectroscopic properties of inorganic and organometallic compounds : techniques, materials and applications : a review of the recent literature.: techniques, materials and applications : a review of the recent literature. Volume 42 ed. by J. Yarwood, Richard Douthwaite, Simon Duckett (2012) - Unknown
No abstract available